Studies in chronic allergic bronchopulmonary aspergillosis. 3. Immunological findings. Issue 3 (June 1977) - Malo, J L; Longbottom, J; Mitchell, J; Hawkins, R; Pepys, J
Abstract : Precipitin tests by two different methods, double-diffusion (DD) and counterimmunoelectrophoresis (CIE), and measurements of total and specific IgE against Aspergillus fumigatus were made in 50 patients with chronic allergic bronchopulmonary aspergillosis and in three control groups--atopics with a positive immediate prick test to A. fumigatus but no evidence of allergic aspergillosis, atopics with a negative prick test to A. fumigatus, and non-atopics. Precipitins were found in 84% and 78% of the patients with aspergillosis by the DD and CIE methods respectively. Precipitins were also found in 6 out of 27 (22%) patients with a positive prick test to A. fumigatus but no evidence of aspergillosis and in 1 of 24 patients with a negative prick test to A. fumigatus. The means of specific and total IgE values were significantly higher in the group of patients with aspergillosis than in the three other groups of patients. The increase in specific but not total IgE showed a statistically significant correlation with positive precipitin tests in the patients with aspergillosis. Total IgE but not specific IgE values were significantly higher (0-02 less than P less than 0-05) in patients who had had a transient radiographic shadow in the previous three months. Positive precipitin tests were also significantly correlated with the number of transient shadows in the past and with the interval of time since the last transient shadow.